Android-Based Inventory System for Sitayu Paint Shop to Optimize Goods Management - Muhamad Alda; Silvi Indryani; Diah Ayu Rina Sari; Tasya syalsabilla; Maulidya Putri Kinanti Ritonga (International Journal Software Engineering and Computer Science (IJSECS), 2025)
The Android-based Paint Shop Inventory Information System was developed to overcome the challenges of managing stock in Sitayu Paint more accurately, efficiently, and organized. This research aims to optimize the process of recording, monitoring, and inventory administration through a mobile application that can be accessed at any time. Using the waterfall development method, this research includes the stages of needs analysis, system design, implementation, verification, and maintenance. The app offers a variety of key features such as minimum stock notifications to prevent stockouts, integrated sales reports, and simple data analysis to support strategic decision-making. The system allows store staff to monitor and update inventory data in real-time, providing high flexibility in daily operations. The implementation results show that the application is able to reduce the risk of recording errors to speed up the work process. and improve time efficiency in inventory management. In addition, this system supports management in developing business strategies based on more organized and relevant data. With the application of this digital technology, Sitayu Paint has succeeded in increasing customer satisfaction through guaranteed product availability and more professional operations. This research makes a significant contribution to modern inventory management in the retail sector, especially paint shops, with the potential for development for the integration of further features such as stock demand prediction